(untitled) (Gilgameš, 2019)
After an attempt to clarify the general concept of ‘piano school’ in both its pedagogical and interpretative meaning, the article presents the most recent research results concerning the pianist, composer and pedagogue Vincenzo Appiani (Monza, 1850 – Milano, 1932), an outstanding representative of the Milanese piano tradition. The paper includes a biographical sketch of the musician and a first reconstruction of his artistical and teaching activities in the wider context of the new physiological achievements in piano technique - arm weight, wrist mobility asf. - and their influences in Italy at the beginning of the XX c.